Sri Lanka : Recapturing Missed Opportunities - World Bank (Washington, DC, 2013)
Despite its healthy economic growth, due to good macroeconomic management, and progress in trade liberalization, Sri Lanka's development is perceived to be well below its potential. Certainly, the civil conflict has taken a heavy social, and economic toll on the country's performance, but also governance, and public institutions have weakened, though maintaining a dominance on the financial sector, and utilities, which further exacerbates productivity, having lost opportunities, in terms of growth, and employment. The study examines recent economic, and social performance, indicating the priority challenges the country needs to face, and vulnerabilities to overcome. Resolving the civil conflict should be paramount. In addition, the role of government needs to be not only revised, but reduced, through strong policy reforms, reduce the fiscal deficit, improve the structure of expenditures, and remove policy distortions in the labor market. The privatization process needs to be enhanced, through reduced numbers of public institutions, effective decentralization, and addressing governance weaknesses. The dimensions of poverty are addressed, exploring vulnerability, insecurity, and marginal poverty, suggesting governance issues in poverty programs, and issues for future poverty strategy. Above all, success lies in the full collaboration of all stakeholders.